Desenvolvimento de nanopartículas de quitossomas como carreadores gênicos - Garcia, Bianca Bonetto Moreno [UNIFESP] (2019)
Chitososomes are nanoparticles formed by interaction between liposomes and chitosan and have of particular interest for biotech applications due to their properties such as ease of production, low cost, storage stability, biodegradability and low immunogenicity and cytotoxicity. The production and use of chitosomes for several applications has been studied and is promising, because this nanoparticle is formed by a stable ternary complex. However, there are few studies in the literature of interaction of these nanoparticles with DNA, necessitating this study for the possible application of this nanoparticle as a gene carrier. Thus, the aim of this work was to evaluate the effect of arginine-modified chitosan on the formation of chitosomes and to study the interaction between different chitosomes with plasmid DNA pEGFP-N3. For this purpose, chitosan (CH) was modified with arginine (CH-Arg) and different chitosomes were synthesized by the reverse phase evaporation technique by the association of DOTAP/DOPE lipids with different amounts of CH-Arg. Chitosomes were complexed with pEGFP-N3 and their structures were evaluated by electrophoresis, zeta potential, dynamic light scattering, SAXS and isothermal titration calorimetry. In addition, the complexes were tested in vitro for evaluation of the transfection rate and cytotoxicity of the complexes. The results showed that the nanoparticles synthesized had a positive surface charge and average size of 116 nm and were able to complex with the pDNA through exothermic and thermodynamically favored interaction, and this complex remained positive enough not to suffer aggregation. The size, the positive charge of the complex and the stable interaction with the pDNA may have favored the entry of the nanoparticle into the cell by the electrostatic interaction with the membrane and the presence of CH-Arg in the compositions may have improved the efficiency of the endosomal escape, efficient carriers and non-cytotoxic complexes.